Effects of morning caffeine` ingestion on mood states, simple reaction time, and short-term maximal performance on elite judoists - Souissi, M.; Abedelmalek, S.; Chtourou, H.; Atheymen, R.; Hakim, A.; Sahnoun, Z. (Asian Journal of Sports Medicine, 2012)
Purpose: The purpose of the present study was to evaluate the ergogenic effect of caffeine ingestion on mood state, simple reaction time, and muscle power during the Wingate test recorded in the morning on elite Judoists.